Civilization as Disciplinization and the Consequences for Religion and World Politics - Cesari, Jocelyne (The review of faith & international affairs, 2019)
This article argues in favor of Norbert Elias's historical and relational sociology to rehabilitate the notion of civilization in the study of international affairs. Elias's approach has two major advantages. First, it avoids the use of de-historicized models of political development that project a western-centered approach as universal. Second it brings into focus the central role of the nation-state in the shaping of the contemporary religious dimension of politics at the national and international levels. This relational and historical perspective will be applied to the case of postcolonial nation-states to explain the rise and expansion of political Islam from national to global forms of political expression.